Mental health literacy for public employees - Bernardo Oliveira Buta; Antônio Cláudio Pimentel Mota; Vilma V.D. Couto; Benjamin Miranda Tabak (BMC, 2024)
Abstract Purpose Although mental disorders are common in the workplace, they often go unnoticed. There is frequently a gap in the recognition and effective management of these disorders, leading to delayed recovery and worsening conditions. This study evaluates the level of Mental Health Literacy (MHL) among employees of the Finance and Planning Departments in the Federal District, Brazil, and proposes preventive measures and de-stigmatization strategies for mental health in the workplace. Methods MHL among active employees was assessed using the Mental Health Literacy Scale (MHLS), developed by O'Connor and Casey (2015) and validated for Brazilian Portuguese by Buta et al. (2024). The data analysis included descriptive and inferential statistics, with nonparametric tests used to compare MHL across different groups. Results The results showed that 27.6% of participants had adequate literacy, 67.9% had problematic levels, and 4.5% had inadequate levels. Women were observed to have higher literacy levels than men. Additionally, significant variations in literacy levels were noted among individuals with different health conditions; those diagnosed with cancer, depression, or other illnesses had higher literacy than those without diagnosed conditions. Conclusion To address MHL challenges, educational actions such as awareness campaigns, training, and consultancy programs are essential.